URGENSI DEMOKRASI DALAM PENEGAKAN HUKUM DI INDONESIA - Firdaus Firdaus (DIKTUM: Jurnal Syariah dan Hukum, 2013)
The basic principle of democracy that is aimed at establishing guidelines and a system of government that protect the interests of the people-oriented and to fight for the rights of the people, without being partial, in the sense mendominankan one group from the other groups in all aspects of life. Terlaksanaya a good legal system and moral will give birth to a democratic system that is authoritative, then the proper creation of the bureaucratic system of government in the sense that a good democracy, the implementation of the application must berekses legal value that is consistent with the will of the meaning of democracy. The law has a high enough benefit in the struggle of human life. To that end, the rules that are in it to make a change or transformation of the legal value of a democracy on any order of statehood